Analysis of Mental Health Nursing Clinical Practice on Mr. H with Positive Affirmation Therapy Innovation on Changes in Signs and Symptoms of Chronic Low Self-Esteem in the Elang Ward, Atma Husada Mahakam Mental Hospital, Samarinda - Desma Ramadini; Dwi Rahmah Fitriani; Arief Budiman; Milkhatun Milkhatun (International Journal of Health Engineering and Technology, 2026)
Low self-esteem is a common mental health nursing problem among patients with severe mental disorders and has a significant impact on self-evaluation, self-confidence, and social functioning. This study aims to examine mental health nursing clinical practice in Mr. H through the application of positive affirmation therapy as an innovative intervention to reduce signs and symptoms of low self-esteem in the Elang Ward of Atma Husada Mahakam Mental Hospital, Samarinda. The method used was a case study with a mental health nursing care process approach, including assessment, nursing diagnosis determination, care planning, implementation, and evaluation. Positive affirmation therapy was applied in a structured manner as a non-pharmacological nursing intervention. The results showed a reduction in signs and symptoms of low self-esteem, accompanied by improvements in the client’s ability to recognize personal strengths, develop self-confidence, and increase participation in activities and social interactions. Based on these findings, positive affirmation therapy is recommended as a supportive intervention in mental health nursing care for clients with low self-esteem and may be further developed in psychiatric nursing practice within mental health hospitals.